Mismatch repair deficient cancers: diagnosis, treatment and prevention - Burn, John (Henry Stewart Talks, 2014)
Lynch syndrome (underlying single gene defect), Microsatellites, Important genes containing repeat sequences, MSI testing (5 marker panel), Mismatch repair (MMR), The genomic pathogenesis of colorectal cancer (CRC), EGFR and BRAF mutant inhibition, BRAF colon cancer project, Methotrexate & MMR deficient tumours, Africans & bowel cancer (Dennis Burkitt), Cancer prevention program (CaPP), NSAIDs and reduced colorectal cancer risk, Aspirin effect on polyps in FAP and colorectal adenoma, The prevention paradox, CaPP2 (Colorectal & Lynch syndrome cancers), Meta-analysis of cancer deaths with aspirin treatment, CRCs in people on aspirin (mostly COX2 negative), Individual response to aspirin in cancer prevention, History of salicylate as an essential nutrient, CaPP3 study, Peptides created by slippage in microsatellite coding, Antibodies as a possible biomarker for Lynch syndrome, The Micoryx vaccine
Archived at 2023/11/30